Critical Thinking Skills: Content, Essence, History, and Components - Xasanova , Shohista; Moydinova , Elmira (The Lingua Spectrum, 2025)
This article discusses the scientific and theoretical foundations of critical thinking, its formation, and the definitions provided by various scholars. Thinking is a cognitive activity inherent to humans that develops over time in different stages. Critical thinking, in turn, is viewed as a process of analyzing, evaluating, and solving problems. The article analyzes various approaches to critical thinking from ancient Greek philosophers to contemporary scholars. Researchers such as Siegel, Halpern, Walsh, and Paul define critical thinking as elements like skills, tendencies, and systematic analysis. Furthermore, the necessity of introducing and systematically mastering critical thinking in education is emphasized. The article thoroughly expresses the theoretical foundations and methodological approaches to critical thinking.